Composite lubricating oil repairing additive and preparation method thereof
By adding components such as sodium dodecylbenzene sulfonate, methyl acrylate, methyl silicone oil, quaternary ammonium modified imidazoline, barium sulfonate and modified chitosan to the lubricating oil to form a protective film, which solves the problem that lubricating oil is prone to rust after long-term use, and achieves better anti-rust and lubricating effects.
Patent Information
- Application Number
- CN202510001784.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Existing lubricants are easily contaminated by air dust after long-term use, resulting in accelerated corrosion of mechanical equipment and inability to use normally, and the existing water-based lubricants have poor anti-rust effect.
Composite lubricant repair additives, including sodium dodecylbenzene sulfonate, methyl acrylate, methyl silicone oil, quaternary ammonium modified imidazoline, barium sulfonate and modified chitosan, are used to form a protective film through the interaction of these components to prevent metal corrosion.
It significantly improves the anti-rust effect and lubricating performance of lubricating oil, and extends the service life of mechanical equipment.
Smart Images

Figure BDA0005225501600000081 
Figure BDA0005225501600000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating oils, in particular to a composite lubricating oil repair additive and a preparation method thereof. Background Art
[0002] Lubricating oil is a liquid lubricant used in automobiles and mechanical equipment to reduce friction and protect machinery and processed parts. During long-term use of lubricating oil, the quality of the oil will be contaminated by dust in the air, which will further accelerate the corrosion of mechanical equipment, thereby causing it to be unable to be used normally. There is a need for a repair composite additive to be added to the lubricating oil to be repaired to repair the problem that it cannot be used normally. For example, patent CN101591584B discloses a water-based lubricating oil and a preparation method thereof. The water-based lubricating oil provided by the invention is suitable for lubrication of mechanical parts such as gears, and has a good lubrication effect, but its anti-rust effect is not good. Summary of the invention
[0003] 1. Technical issues to be solved
[0004] In view of the deficiencies of the prior art, the present invention provides a composite lubricating oil repair additive and a preparation method thereof, which has good rust prevention and lubrication effects.
[0005] (II) Technical solution
[0006] To achieve the above object, the present invention provides the following technical solution: a composite lubricating oil repair additive, comprising the following components by weight: 2-4 parts by weight of sodium dodecylbenzene sulfonate, 1-2 parts by weight of methyl acrylate, 15-25 parts by weight of methyl silicone oil, 2-5 parts by weight of quaternary ammonium salt-modified imidazoline, 4-5 parts by weight of barium sulfonate, 3-6 parts by weight of modified chitosan, and 1.2-1.6 parts by weight of zinc dialkyl dithiophosphate;
[0007] The preparation method of the modified imidazoline is
[0008] Step 1: add triethylenetetramine into a reactor, heat it to 100-120°C, then continue to add oleic acid, continue to heat it to 145-150°C, react until no water is generated, then heat it to 230-240°C to react for 6-8h, and after the reaction is completed, distill under reduced pressure to obtain intermediate 1;
[0009] Step 2: Add intermediate 1 and 3-chloro-1,2-propylene glycol to acetone solvent, stir evenly, react at 70-95°C for 6-10h, wash and dry after reaction to obtain quaternized imidazoline;
[0010] Step 3: Add L-lysine and quaternized imidazoline to N,N-dimethylformamide solvent, stir and mix, continue to add p-toluenesulfonic acid catalyst, react at 75-95°C for 5-8h, and then distill under reduced pressure and wash to obtain amino-modified quaternized imidazoline;
[0011] Step 4: Add 4-9 parts by weight of amino-modified quaternized imidazoline and 5-13 parts by weight of 1,3-propane sultone to acetone solvent for dissolution, then dropwise add a sodium hydroxide solution with a concentration of 3-5 mol / L, react at 70-90° C., concentrate under reduced pressure after the reaction to remove the solvent, and recrystallize the crude product in ethanol to obtain a modified imidazoline.
[0012] Preferably, in step 1, the mass ratio of triethylenetetramine to oleic acid is 2.1-2.3:1.
[0013] Preferably, in the step 2, the mass ratio of the intermediate 1:3-chloro-1,2-propylene glycol is 1:1.2-1.5.
[0014] Preferably, in step 3, the mass ratio of L-lysine, quaternized imidazoline and p-toluenesulfonic acid catalyst is 0.8-1.1:1:0.02-0.04.
[0015] Preferably, the reaction time in step 4 is 6-8h.
[0016] Preferably, the preparation method of the modified chitosan is:
[0017] S1. Add 7-10 parts by weight of chitosan acetic acid aqueous solution to the reactor, heat in a water bath at 75-100 ° C, add 5-8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at constant pressure, react, wash with anhydrous ethanol after the reaction, dry, dialyze, and concentrate to obtain quaternized chitosan;
[0018] S2. Add 5-8 parts by weight of quaternized chitosan, 6-14 parts by weight of coconut oil hydroxyethyl imidazoline, and 7-10 parts by weight of adipoyl chloride to N,N-dimethylformamide solvent, stir for 2-4 minutes, continue to add 0.01-0.03 parts by weight of pyridine catalyst, react at 80-90°C for 4-7 hours, and then distill under reduced pressure and wash to obtain modified chitosan.
[0019] Preferably, the reaction time in S1 is 4-7h.
[0020] Preferably, the preparation method of the composite lubricating oil repair additive is: add methyl silicone oil, sodium dodecylbenzene sulfonate, methyl acrylate, zinc dialkyl dithiophosphate, and barium sulfonate into a stirrer, stir at 90-95°C for 2-4 minutes, continue to add quaternary ammonium salt modified imidazoline and modified chitosan, stir at 75-95°C for 2-6 minutes, and then obtain the composite lubricating oil repair additive.
[0021] (III) Beneficial technical effects
[0022] The invention provides a composite lubricating oil repair additive by adding methyl silicone oil, sodium dodecylbenzene sulfonate, methyl acrylate, zinc dialkyl dithiophosphate and barium sulfonate into a stirrer, stirring, and then adding quaternary ammonium salt modified imidazoline and modified chitosan, stirring, and then obtaining the composite lubricating oil repair additive.
[0023] Triethylenetetramine and oleic acid are subjected to a cyclization reaction to generate an imidazoline group, and a tertiary amine group is introduced to obtain intermediate 1; the tertiary amine group of intermediate 1 is reacted with chlorine in 3-chloro-1,2-propanediol to generate a quaternary ammonium salt group, and a hydroxyl group is introduced to obtain quaternized imidazoline; the carboxyl group in L-lysine and the hydroxyl group in the quaternized imidazoline are subjected to an esterification reaction to introduce an amino group to obtain an amino-modified quaternized imidazoline; the amino group in the amino-modified quaternized imidazoline is reacted with 1,3-propane sultone to introduce a sodium sulfonate group to obtain a modified imidazoline.
[0024] The chitosan molecular structure in the modified chitosan contains a large number of amino groups, which can chelate with metal ions to form a protective film on the metal surface, prevent the dissolution and migration of metal ions, and further reduce the corrosion of the metal. At the same time, chitosan also has good adsorption film-forming properties, can form a dense protective film on the metal surface, isolate air and moisture, prevent metal oxidation and rust, and add it to lubricating oil to improve its anti-rust effect. The imidazoline in the quaternary ammonium salt modified imidazoline can form a protective film on the metal surface, effectively prevent the metal from contacting with the corrosive medium, thereby slowing down the corrosion process of the metal, thereby achieving a good anti-rust effect. The quaternary ammonium salt group forms a protective film on the metal surface to prevent moisture, oxygen and other corrosive substances from contacting the metal, thereby effectively preventing the metal from rusting. The sodium sulfonate group forms a protective film on the metal surface to isolate oxygen and moisture in the air, thereby slowing down the corrosion process of the metal and achieving an anti-rust effect.
[0025] In the present invention, the hydroxyl group in the quaternized chitosan, the hydroxyl group in the coconut oil hydroxyethyl imidazoline and the acyl chloride group in the adipoyl chloride react to obtain the modified chitosan; the substitution degree of the quaternary ammonium salt and the imidazoline is further increased, so that the rust prevention effect is better. At the same time, the quaternary ammonium salt modified imidazoline, the quaternary ammonium salt group in the modified chitosan, the sodium sulfonate group and the chitosan molecular structure can all improve the lubricating effect of the lubricating oil. DETAILED DESCRIPTION
[0026] Example 1
[0027] Preparation of chitosan acetic acid aqueous solution: Weigh 1 part by weight of chitosan and disperse it in 50 parts by weight of water, and put it into a reactor, raise the temperature to 60°C, slowly add 4 parts by weight of 10% acetic acid aqueous solution and stir thoroughly to dissolve the chitosan, and obtain chitosan acetic acid aqueous solution. In the present invention, the mass percentage concentration of chitosan in the chitosan acetic acid aqueous solution is 3%.
[0028] (1) triethylenetetramine was added to a reactor, the temperature was raised to 100° C., and then oleic acid was added thereto, wherein the mass ratio of triethylenetetramine to oleic acid was 2.1:1, the temperature was further raised to 145° C., and the reaction was continued until no water was generated, and the temperature was then raised to 230° C. and the reaction was continued for 6 hours. After the reaction was completed, the reaction was distilled under reduced pressure to obtain an intermediate 1;
[0029] (2) adding intermediate 1 and 3-chloro-1,2-propylene glycol to an acetone solvent, wherein the mass ratio of intermediate 1 to 3-chloro-1,2-propylene glycol is 1:1.2, stirring evenly, reacting at 70° C. for 6 h, washing after reaction, and drying to obtain a quaternized imidazoline;
[0030] (3) adding L-lysine and quaternized imidazoline to N,N-dimethylformamide solvent, stirring and mixing, and continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of L-lysine, quaternized imidazoline, and p-toluenesulfonic acid catalyst is 0.8:1:0.02, reacting at 75° C. for 5 h, and then performing reduced pressure distillation and washing to obtain amino-modified quaternized imidazoline;
[0031] (4) adding 4 parts by weight of amino-modified quaternized imidazoline and 5 parts by weight of 1,3-propane sultone to an acetone solvent for dissolution, then dropping a 3 mol / L sodium hydroxide solution, reacting at 70° C. for 6 h, concentrating under reduced pressure to remove the solvent after the reaction, and recrystallizing the crude product in ethanol to obtain a modified imidazoline;
[0032] (5) adding 7 parts by weight of chitosan acetic acid aqueous solution to the reactor, heating in a water bath at 75° C., adding 5 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at a constant pressure, reacting for 4 hours, washing with anhydrous ethanol after the reaction, drying, dialyzing, and concentrating to obtain quaternized chitosan;
[0033] (6) adding 5 parts by weight of quaternized chitosan, 6 parts by weight of coconut oil hydroxyethyl imidazoline, and 7 parts by weight of adipoyl chloride to N,N-dimethylformamide solvent, stirring for 2 minutes, and then adding 0.01 parts by weight of pyridine catalyst, reacting at 80° C. for 4 hours, and then distilling under reduced pressure and washing to obtain modified chitosan;
[0034] (7) 15 parts by weight of methyl silicone oil, 2 parts by weight of sodium dodecylbenzene sulfonate, 1 part by weight of methyl acrylate, 1.2 parts by weight of zinc dialkyl dithiophosphate, and 4 parts by weight of barium sulfonate are added into a stirrer and stirred at 90° C. for 2 min. Then, 2 parts by weight of quaternary ammonium salt-modified imidazoline and 3 parts by weight of modified chitosan are added thereto and stirred at 75° C. for 2 min. After the mixture is stirred, a composite lubricating oil repair additive is obtained.
[0035] Example 2
[0036] (1) Triethylenetetramine is added to a reactor, the temperature is raised to 120° C., and then oleic acid is added thereto, wherein the mass ratio of triethylenetetramine to oleic acid is 2.3:1, the temperature is further raised to 150° C., and the reaction is carried out until no water is generated, and the temperature is then raised to 240° C. and the reaction is carried out for 8 hours. After the reaction is completed, the reaction is carried out under reduced pressure distillation to obtain intermediate 1;
[0037] (2) adding intermediate 1 and 3-chloro-1,2-propylene glycol to an acetone solvent, wherein the mass ratio of intermediate 1 to 3-chloro-1,2-propylene glycol is 1:1.5, stirring evenly, reacting at 95° C. for 10 h, washing after reaction, and drying to obtain a quaternized imidazoline;
[0038] (3) adding L-lysine and quaternized imidazoline to N,N-dimethylformamide solvent, stirring and mixing, and continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of L-lysine, quaternized imidazoline, and p-toluenesulfonic acid catalyst is 1.1:1:0.04, reacting at 95° C. for 8 h, and then performing reduced pressure distillation and washing to obtain amino-modified quaternized imidazoline;
[0039] (4) adding 9 parts by weight of amino-modified quaternized imidazoline and 13 parts by weight of 1,3-propane sultone to an acetone solvent for dissolution, then dropping a 5 mol / L sodium hydroxide solution, reacting at 90° C. for 8 h, concentrating under reduced pressure to remove the solvent after the reaction, and recrystallizing the crude product in ethanol to obtain a modified imidazoline;
[0040] (5) adding 10 parts by weight of chitosan acetic acid aqueous solution to the reactor, heating in a water bath at 100° C., adding 8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at a constant pressure, reacting for 7 hours, washing with anhydrous ethanol after the reaction, drying, dialyzing, and concentrating to obtain quaternized chitosan;
[0041] (6) adding 8 parts by weight of quaternized chitosan, 14 parts by weight of coconut oil hydroxyethyl imidazoline, and 10 parts by weight of adipoyl chloride to N,N-dimethylformamide solvent, stirring for 4 minutes, and then adding 0.03 parts by weight of pyridine catalyst, reacting at 90° C. for 7 hours, and then distilling under reduced pressure and washing to obtain modified chitosan;
[0042] (7) 25 parts by weight of methyl silicone oil, 4 parts by weight of sodium dodecylbenzene sulfonate, 2 parts by weight of methyl acrylate, 1.6 parts by weight of zinc dialkyl dithiophosphate, and 5 parts by weight of barium sulfonate are added into a stirrer and stirred at 95° C. for 4 min. Then, 5 parts by weight of quaternary ammonium salt-modified imidazoline and 6 parts by weight of modified chitosan are added thereto and stirred at 95° C. for 6 min. After the mixture is stirred, a composite lubricating oil repair additive is obtained.
[0043] Example 3
[0044] (1) adding triethylenetetramine to a reactor, heating the reactor to 100-120° C., and then adding oleic acid, wherein the mass ratio of triethylenetetramine to oleic acid is 2.1-2.3:1, and heating the reactor to 145-150° C., reacting until no water is generated, and then heating the reactor to 230-240° C., reacting the reactor for 6-8 hours, and distilling the reactor under reduced pressure after the reaction is completed to obtain an intermediate 1;
[0045] (2) adding intermediate 1 and 3-chloro-1,2-propylene glycol to an acetone solvent, wherein the mass ratio of intermediate 1 to 3-chloro-1,2-propylene glycol is 1:1.4, stirring evenly, reacting at 85° C. for 8 h, washing after reaction, and drying to obtain a quaternized imidazoline;
[0046] (3) adding L-lysine and quaternized imidazoline to N,N-dimethylformamide solvent, stirring and mixing, and continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of L-lysine, quaternized imidazoline, and p-toluenesulfonic acid catalyst is 0.9:1:0.03, reacting at 85° C. for 7 h, and then performing reduced pressure distillation and washing to obtain amino-modified quaternized imidazoline;
[0047] (4) adding 7 parts by weight of amino-modified quaternized imidazoline and 10 parts by weight of 1,3-propane sultone to an acetone solvent for dissolution, then dropping a 4 mol / L sodium hydroxide solution, reacting at 80° C. for 7 h, concentrating under reduced pressure to remove the solvent after the reaction, and recrystallizing the crude product in ethanol to obtain a modified imidazoline;
[0048] (5) adding 8 parts by weight of chitosan acetic acid aqueous solution to the reactor, heating in a water bath at 85° C., adding 6 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at a constant pressure, reacting for 5 hours, washing with anhydrous ethanol after the reaction, drying, dialyzing, and concentrating to obtain quaternized chitosan;
[0049] (6) adding 7 parts by weight of quaternized chitosan, 10 parts by weight of coconut oil hydroxyethyl imidazoline, and 8 parts by weight of adipoyl chloride to N,N-dimethylformamide solvent, stirring for 3 minutes, and then adding 0.02 parts by weight of pyridine catalyst, reacting at 85° C. for 6 hours, and then distilling under reduced pressure and washing to obtain modified chitosan;
[0050] (7) 20 parts by weight of methyl silicone oil, 3 parts by weight of sodium dodecylbenzene sulfonate, 1.5 parts by weight of methyl acrylate, 1.5 parts by weight of zinc dialkyl dithiophosphate, and 4 parts by weight of barium sulfonate are added into a stirrer and stirred at 95° C. for 3 min. Then, 45 parts by weight of quaternary ammonium salt-modified imidazoline and 5 parts by weight of modified chitosan are added thereto and stirred at 85° C. for 4 min. After the mixture is stirred, a composite lubricating oil repair additive is obtained.
[0051] Example 4
[0052] (1) triethylenetetramine was added to a reactor, the temperature was raised to 100° C., and then oleic acid was added thereto, wherein the mass ratio of triethylenetetramine to oleic acid was 2.1:1, the temperature was further raised to 145° C., and the reaction was continued until no water was generated, and the temperature was then raised to 230° C. and the reaction was continued for 6 hours. After the reaction was completed, the reaction was distilled under reduced pressure to obtain an intermediate 1;
[0053] (2) adding intermediate 1 and 3-chloro-1,2-propylene glycol to an acetone solvent, wherein the mass ratio of intermediate 1 to 3-chloro-1,2-propylene glycol is 1:1.2, stirring evenly, reacting at 70° C. for 6 h, washing after reaction, and drying to obtain a quaternized imidazoline;
[0054] (3) adding L-lysine and quaternized imidazoline to N,N-dimethylformamide solvent, stirring and mixing, and continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of L-lysine, quaternized imidazoline, and p-toluenesulfonic acid catalyst is 1.1:1:0.04, reacting at 95° C. for 8 h, and then performing reduced pressure distillation and washing to obtain amino-modified quaternized imidazoline;
[0055] (4) adding 9 parts by weight of amino-modified quaternized imidazoline and 13 parts by weight of 1,3-propane sultone to an acetone solvent for dissolution, then dropping a 5 mol / L sodium hydroxide solution, reacting at 90° C. for 8 h, concentrating under reduced pressure to remove the solvent after the reaction, and recrystallizing the crude product in ethanol to obtain a modified imidazoline;
[0056] (5) adding 9 parts by weight of chitosan acetic acid aqueous solution to the reactor, heating in a water bath at 80° C., adding 6 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at a constant pressure, reacting for 4 hours, washing with anhydrous ethanol after the reaction, drying, dialyzing, and concentrating to obtain quaternized chitosan;
[0057] (6) adding 7 parts by weight of quaternized chitosan, 10 parts by weight of coconut oil hydroxyethyl imidazoline, and 8 parts by weight of adipoyl chloride to N,N-dimethylformamide solvent, stirring for 3 minutes, and then adding 0.02 parts by weight of pyridine catalyst, reacting at 85° C. for 6 hours, and then distilling under reduced pressure and washing to obtain modified chitosan;
[0058] (7) 20 parts by weight of methyl silicone oil, 3 parts by weight of sodium dodecylbenzene sulfonate, 1.5 parts by weight of methyl acrylate, 1.5 parts by weight of zinc dialkyl dithiophosphate, and 4 parts by weight of barium sulfonate are added into a stirrer and stirred at 95° C. for 3 min. Then, 45 parts by weight of quaternary ammonium salt-modified imidazoline and 5 parts by weight of modified chitosan are added thereto and stirred at 85° C. for 4 min. After the mixture is stirred, a composite lubricating oil repair additive is obtained.
[0059] Comparative Example 1
[0060] Compared with Example 4, this comparative example is different in that no quaternary ammonium salt-modified imidazoline is added.
[0061] Comparative Example 2
[0062] Compared with Example 4, this comparative example is different in that no modified chitosan is added.
[0063] The lubricating oils of Examples 1-4 were subjected to an anti-rust salt spray test according to GB / T10125-97. The lubricating oils were applied to cold-rolled carbon steel plates at a coating amount of 5 g / m2. The specific test results are shown in Table 1.
[0064] Table 1: Anti-rust performance test.
[0065]
[0066]
[0067] It can be seen from Table 1 that Examples 1-4 of the present invention have better anti-rust effects than Comparative Examples 1-2.
[0068] Load-bearing capacity test: carried out in accordance with GB / T3142-1982. Test conditions: speed 1450 rpm, test time 10s, load 392N. Steel ball conforms to G308, grade II bearing steel ball, diameter 12.7mm, material GCr15. The test instrument is a four-ball extreme pressure tester of model MRS provided by Jinan Star Test Technology Co., Ltd.
[0069] Table 2: Load-bearing capacity test.
[0070] project <![CDATA[Sintering load (P D ,]]> Example 1 1875 Example 2 1884 Example 3 1867 Example 4 1871 Comparative Example 1 1802 Comparative Example 2 1805
[0071] It can be seen from Table 2 that Examples 1-4 of the present invention have better load-bearing capacity than Comparative Examples 1-2, indicating better lubrication effect.
[0072] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A composite lubricating oil repair additive, characterized in that: The invention comprises the following components by weight: 2-4 parts by weight of sodium dodecylbenzene sulfonate, 1-2 parts by weight of methyl acrylate, 15-25 parts by weight of methyl silicone oil, 2-5 parts by weight of quaternary ammonium salt-modified imidazoline, 4-5 parts by weight of barium sulfonate, 3-6 parts by weight of modified chitosan, and 1.2-1.6 parts by weight of zinc dialkyl dithiophosphate; The preparation method of the modified imidazoline is Step 1: add triethylenetetramine into a reactor, heat it to 100-120°C, then continue to add oleic acid, continue to heat it to 145-150°C, react until no water is generated, then heat it to 230-240°C to react for 6-8h, and after the reaction is completed, distill under reduced pressure to obtain intermediate 1; Step 2: Add intermediate 1 and 3-chloro-1,2-propylene glycol to acetone solvent, stir evenly, react at 70-95°C for 6-10h, wash and dry after reaction to obtain quaternized imidazoline; Step 3: Add L-lysine and quaternized imidazoline to N,N-dimethylformamide solvent, stir and mix, continue to add p-toluenesulfonic acid catalyst, react at 75-95°C for 5-8h, and then distill under reduced pressure and wash to obtain amino-modified quaternized imidazoline; Step 4: Add 4-9 parts by weight of amino-modified quaternized imidazoline and 5-13 parts by weight of 1,3-propane sultone to acetone solvent for dissolution, then dropwise add a sodium hydroxide solution with a concentration of 3-5 mol / L, react at 70-90° C., concentrate under reduced pressure after the reaction to remove the solvent, and recrystallize the crude product in ethanol to obtain a modified imidazoline.
2. The composite lubricating oil repair additive according to claim 1, characterized in that: In the step 1, the mass ratio of triethylenetetramine to oleic acid is 2.1-2.3:
1.
3. The composite lubricating oil repair additive according to claim 1, characterized in that: The mass ratio of the intermediate 1 and 3-chloro-1,2-propylene glycol in the step 2 is 1:1.2-1.
5.
4. The composite lubricating oil repair additive according to claim 1, characterized in that: In the step 3, the mass ratio of L-lysine, quaternized imidazoline and p-toluenesulfonic acid catalyst is 0.8-1.1:1:0.02-0.
04.
5. The composite lubricating oil repair additive according to claim 1, characterized in that: The reaction time in step 4 is 6-8h.
6. The composite lubricating oil repair additive according to claim 1, characterized in that: The preparation method of the modified chitosan is: S1. Add 7-10 parts by weight of chitosan acetic acid aqueous solution to the reactor, heat in a water bath at 75-100 ° C, add 5-8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at constant pressure, react, wash with anhydrous ethanol after the reaction, dry, dialyze, and concentrate to obtain quaternized chitosan; S2. Add 5-8 parts by weight of quaternized chitosan, 6-14 parts by weight of coconut oil hydroxyethyl imidazoline, and 7-10 parts by weight of adipoyl chloride to N,N-dimethylformamide solvent, stir for 2-4 minutes, continue to add 0.01-0.03 parts by weight of pyridine catalyst, react at 80-90°C for 4-7 hours, and then distill under reduced pressure and wash to obtain modified chitosan.
7. The composite lubricating oil repair additive according to claim 6, characterized in that: The reaction time in S1 is 4-7h.
8. A method for preparing the composite lubricating oil repair additive according to any one of claims 1 to 7, characterized in that: The preparation method of the composite lubricating oil repair additive is as follows: methyl silicone oil, sodium dodecylbenzene sulfonate, methyl acrylate, zinc dialkyl dithiophosphate and barium sulfonate are added into a stirrer, stirred at 90-95° C. for 2-4 minutes, quaternary ammonium salt-modified imidazoline and modified chitosan are added thereto, stirred at 75-95° C. for 2-6 minutes, and the composite lubricating oil repair additive is obtained after the stirring.
Citation Information
Patent Citations
Water-base lubricant and preparation method thereof
CN101591584B
Polyisobutene gas phase slow-release rust protection oil and preparation method thereof
CN103045330A
Gemini imidazoline corrosion inhibitor and preparation method thereof
CN111574453A
Composite lubricating oil repairing additive and preparation method thereof
CN114958470A
Water-soluble lubricating antirust agent and preparation method thereof
CN117844561A
Cited By
Antibacterial modified plastic and preparation method thereof
CN120665370A